ANALISIS PELAKSANAAN BIMBINGAN KARIR PADA PESERTA DIDIK KELAS IX SMP NEGERI 12 PONTIANAK - Prayoga, Yanda; Asrori, Mohammad; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCareer counseling is an aid in preparing for the world of work, job selection or occupation (profession) and provide certain self-ready to take the position and in adjusting to the demands of the job that has been entered. Career guidance conducted by guidance and counseling teachers aims to assist learners in obtaining the necessary competencies, then with the guidance of a career will help learners in entering life, lifestyle and events in life. One that is expected in the implementation of career guidance is to produce people who have been educated, especially referring to the transition of school to the world of work in experiencing various activities. Therefore, researchers want to improve the quality of career guidance services to students in class IX SMP Negeri 12 Pontianak. The problem in this study is